PATHOBIOLOGY OF HODGKIN LYMPHOMA - Claudio Agostinelli; Stefano Pileri (Mediterranean Journal of Hematology and Infectious Diseases, 2014)
Hodgkin’s lymphoma is a lymphoid tumour that represents about 1% of all de novo neoplasms occurring every year worldwide. Its diagnosis is based on the identification of characteristic neoplastic cells within an inflammatory milieu. Molecular studies have shown that most, if not all cases, belong to the same clonal population, which is derived from peripheral B-cells. The relevance of Epstein-Barr virus infection at least in a proportion of patients was also demonstrated. The REAL/WHO classification recognizes a basic distinction between nodular lymphocyte predominance  HL (NLPHL) and classic HL (CHL), reflecting the differences in clinical presentation, behavior, morphology, phenotype, molecular features as well as in the composition of their cellular background. CHL has been classified into four subtypes: lymphocyte rich, nodular sclerosing, mixed cellularity and lymphocyte depleted. Despite its well known histological and clinical features, Hodgkin's lymphoma (HL) has recently been the object of intense research activity, leading to a better understanding of its phenotype, molecular characteristics and possible mechanisms of lymphomagenesis.